2014
DOI: 10.5195/palrap.2014.67
|View full text |Cite
|
Sign up to set email alerts
|

Capture All the URLs: First Steps in Web Archiving

Abstract: As higher education embraces new technologies, university activities-including teaching, learning, and research-increasingly take place on university websites, on universityrelated social media pages, and elsewhere on the open Web. Despite perceptions that "once it's on the Web, it's there forever," this dynamic digital content is highly vulnerable to degradation and loss. In order to preserve and provide enduring access to this complex body of university records, archivists and librarians must rise to the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Studies have reported the involvement of academic institutions in web archiving initiatives such as the Queens University Canada (Heil and Jin, 2017), Wake Forest University (Fansler et al, 2014), University of Toronto (Milligan, 2016), State and University Library Denmark (Sutton, 2004), Drexel University, Slippery Rock University, and the University of Scranton (Antracoli et al, 2014). This is contrary to the findings of Khumalo and Nkala (2015), which revealed that, apart from the lack of awareness of the respondents about web archiving, African institutions are not involved in web archiving initiatives to harvest their institutional repositories for future use.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have reported the involvement of academic institutions in web archiving initiatives such as the Queens University Canada (Heil and Jin, 2017), Wake Forest University (Fansler et al, 2014), University of Toronto (Milligan, 2016), State and University Library Denmark (Sutton, 2004), Drexel University, Slippery Rock University, and the University of Scranton (Antracoli et al, 2014). This is contrary to the findings of Khumalo and Nkala (2015), which revealed that, apart from the lack of awareness of the respondents about web archiving, African institutions are not involved in web archiving initiatives to harvest their institutional repositories for future use.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The collaborative effort between Drexel University, Slippery Rock University, and the University of Scranton is also a good example of how academic institutions have been able to embark on successful Web archiving initiatives through collaboration (Antracoli et al, 2014). The New York Art Consortium (NYARC) is also able to collaborate to collect, preserve and provide access to “art ephemera born in digital formats native to the web” Duncan and Blumenthal (2016: 116).…”
Section: Web Archiving Policymentioning
confidence: 99%
See 1 more Smart Citation
“…NYARC will partner with DuraCloud during the second year of the grant to Ideally, die implementation of a quality assurance programme ensures that the Web content crawled by die institution has been accurately and completely archived so that die capture includes not only H T M L content but also the look and feel of the site, as well as embedded documents and audiovisual materials. 6 With permission from staff of The Isamu Noguchi Catalogue Raisonne, NYARC has included die P D F version in our Archive-It collection, where it serves as documentation of the catalogue as it existed in summer 2014. We will continue to archive this catalogue raisonne over time, with frequency of capture mirroring the schedule of update to information made publicly viewable widiin die catalogue.…”
Section: E X P L O R E Collecting O R G a N I Z A T I O N S |Rnd An Omentioning
confidence: 99%